Desvendando as paisagens no ensino de geografia a partir do uso e ocupação do solo - Nascimento, Márcio Silveira (2019)
The complexity of the reality of the world, present in everyday life, receives the teaching of geography, presenting new paradigms of knowledge, in view of the formation of a citizen spatial consciousness. It is a knowledge that teaches geography teaching practices to improve the comprehension teachings of spatial transformations, reaffirming the importance of geography teaching in contributing to the formation of students who understand and recognize the importance of their participation in the participation of space. In this exhibition, this dissertation presents studies on the creation of a didactic proposal for the teaching of “landscape”, associating with the use and occupation of the soil, a strategy of valorization as students' perceptions about the knowledge of their daily spaces, of something concrete that is in the field of his visions, for a broader and deeper reading / interpretation, recognizing as actions and interactions of man with the living environment, over time. A research has a qualitative approach, where the natural environment, the school environment, as landscapes of the place are as sources of presentations. Seeking to understand the perception of the spatial configuration of the reality of the place, or the research subjects are inserted. Step guide, which includes a sequence of phases to apply: learning diagnosis, intervention and verification. Finally, this research originated an educational product entitled “Pedagogical Kit: Landscape in Sight”, no qualified material for the promotion of classes and / or activities focused on the theme addressed in this research, providing subsidies for teachers who use and develop pedagogical work. . It concludes, therefore, that the activities developed in this work demonstrated as important for landscape teaching, not only include school geography, tolerate new tests of approaches in case of extinction or fragmented teaching and to conceive strategies and possibilities of interrelation or content with other areas school subjects, enabling the education not only of conceptual understanding, but, more broadly and dynamically, the knowledge of processes and phenomena that surround, recognizing the importance of landscape and the elements that compose it.